Ketones Prevent Oxidative Impairment of Hippocampal Synaptic Integrity through K(ATP) Channels - Kim, Do Young (PLoS One, 2015)
Dietary and metabolic therapies are increasingly being considered for a variety of neurological disorders, based in part on growing evidence for the neuroprotective properties of the ketogenic diet (KD) and ketones. Earlier, we demonstrated that ketones afford hippocampal synaptic protection against exogenous oxidative stress, but the mechanisms underlying these actions remain unclear. Recent studies have shown that ketones may modulate neuronal firing through interactions with ATP-sensitive potassium (K(ATP)) channels. Here, we used a combination of electrophysiological, pharmacological, and biochemical assays to determine whether hippocampal synaptic protection by ketones is a consequence of K(ATP) channel activation. Ketones dose-dependently reversed oxidative impairment of hippocampal synaptic integrity, neuronal viability, and bioenergetic capacity, and this action was mirrored by the K(ATP) channel activator diazoxide. Inhibition of K(ATP) channels reversed ketone-evoked hippocampal protection, and genetic ablation of the inwardly rectifying K(+) channel subunit Kir6.2, a critical component of K(ATP) channels, partially negated the synaptic protection afforded by ketones. This partial protection was completely reversed by co-application of the K(ATP) blocker, 5-hydoxydecanoate (5HD). We conclude that, under conditions of oxidative injury, ketones induce synaptic protection in part through activation of K(ATP) channels.